(untitled) (Islas, 2021)
La cristianización del antiguo Reino de los Bakongos constituyó un proceso de interés para entender las variantes religiosas en África y por qué también se trasladaron a América. El catolicismo se extendió en África conjuntamente con la colonización político-cultural. Pero las raíces de las religiones autóctonas se unieron a guerras por el poder dando lugar a variantes religiosas, entre ellas el antonionismo, corriente mesiánica de veneración a San Antonio con características del animismo africano que se traspasa a América, y no es casual que muchos cabildos congos de Cuba veneren a San Antonio, siendo estos rituales herederos del antonionismo africano. The Christianization of the ancient Kingdom of Bakongo was a process of interest to understand the religious variants in Africa, and why they also moved to America. Catholicism spread in Africa together with the political-cultural colonization. Nonetheless, the roots of native religions joined to wars for power, which gave rise to religious variants such as antonionism, a messianic current of veneration for Saint Anthony (San Antonio in Spanish) with characteristics of African animism that is transferred to America; and it is not coincidence that many Congolese cabildos in Cuba venerate Saint Anthony, since these rituals were inherited from African antonionism.